2022
DOI: 10.1186/s12889-022-12898-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis of varicella in Dalian from 2009 to 2019 and application of three kinds of model in prediction prevalence of varicella

Abstract: Objective This study described the epidemic characteristics of varicella in Dalian from 2009 to 2019, explored the fitting effect of Grey model first-order one variable( GM(1,1)), Markov model, and GM(1,1)-Markov model on varicella data, and found the best fitting method for this type of data, to better predict the incidence trend. Methods For this Cross-sectional study, this article was completed in 2020, and the data collection is up to 2019. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…Our findings demonstrated a decrease in varicella incidence from January to March and from June to August, which aligns with previous epidemiological studies conducted in various regions of China, including Shandong Province, Dalian City, Guangzhou City, and Hangzhou City [24][25][26][27]. Cheng et al and Lu et al suggested that this period corresponds to the winter and summer vacations of Chinese students [25,26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings demonstrated a decrease in varicella incidence from January to March and from June to August, which aligns with previous epidemiological studies conducted in various regions of China, including Shandong Province, Dalian City, Guangzhou City, and Hangzhou City [24][25][26][27]. Cheng et al and Lu et al suggested that this period corresponds to the winter and summer vacations of Chinese students [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings demonstrated a decrease in varicella incidence from January to March and from June to August, which aligns with previous epidemiological studies conducted in various regions of China, including Shandong Province, Dalian City, Guangzhou City, and Hangzhou City [ 24 – 27 ]. Cheng et al and Lu et al suggested that this period corresponds to the winter and summer vacations of Chinese students [ 25 , 26 ]. The occurrence of summer and winter holidays in many schools across China during this timeframe led to decreased interactions among children, thereby reducing the likelihood of varicella transmission within educational environments where the virus can easily spread.…”
Section: Discussionmentioning
confidence: 99%
“…As a serious complication of chickenpox, primary varicella pneumonia is estimated to occur in 1 out of 400 infections. [4] As a highly contagious disease, many body systems can be affected such as the lungs, skin, and central nervous system. Smoking can lead to decrease the activation of alveolar macrophages; it will increase the susceptibility to varicella pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…As a serious complication of chickenpox, primary varicella pneumonia is estimated to occur in 1 out of 400 infections. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Outbreaks in China are prevalent in primary school students. [6,7] Varicella remains inactive in the nervous system and may later erupt in adults causing more serious consequences in the form of "shingles" (herpes zoster). [8] Varicella infections are therefore a burden on health authorities' resources.…”
Section: Introductionmentioning
confidence: 99%